Proteomic signature of HIV-associated subclinical left atrial remodeling and incident heart failure - Tess E. Peterson; Virginia S. Hahn; Ruin Moaddel; Min Zhu; Sabina A. Haberlen; Frank J. Palella; Michael Plankey; Joel S. Bader; Joao A. C. Lima; Robert E. Gerszten; Jerome I. Rotter; Stephen S. Rich; et al. (Nature Communications)
Abstract People living with HIV are at higher risk of heart failure and associated left atrial remodeling compared to people without HIV. Mechanisms are unclear but have been linked to inflammation and premature aging. Here we obtain plasma proteomics concurrently with cardiac magnetic resonance imaging in two independent study populations to identify parallels between HIV-related and aging-related immune dysfunction that could contribute to atrial remodeling and clinical heart failure. We discover a plasma proteomic signature that may in part reflect or contribute to HIV-associated atrial remodeling, many features of which are associated with older age and time to incident heart failure among an independent community-based cohort without HIV. This proteomic profile was statistically enriched for immune checkpoint proteins, tumor necrosis factor signaling, ephrin signaling, and extracellular matrix organization, identifying possible shared pathways in HIV and aging that may contribute to risk of heart failure.